Corporate governance after the credit crunch - Mallin, Christine (Henry Stewart Talks, 2011)
Corporate governance and the global financial crisis, Risk management, Corporate collapses and scandals, Institutional shareholders, Internal controls, Cadbury Report, OECD Principles of Corporate Governance, Audit committee, Remuneration (compensation) committee, Nomination (appointments) committee, Duality of CEO/Chair roles, Directors' remuneration, Payment for failure, 'Say on Pay', Stewardship role, Shareholders' rights, Tools of governance, Dialogue, Voting, Shareholder proposals, Focus lists